International architectural workshop Patching the City 2011 - Vasa J. Perović; Anja Vidic (AR: Arhitektura, Raziskave, 2012)
The city of Rijeka is cut off from the sea by a strip of abandoned industrial zones. With the revitalisation of the degraded industrial areas, the city has an opportunity to progress and regain contact with the sea. The project proposed opening the area for public use, whereby the city would have a new urban public space, a city beach. In a few stages, the area could become a secondary city centre on the shoreline.